(untitled) (REGE Revista de Gestão, 2013)
The main purpose of this research is to identify whether the Higher Education Institutions (HEIs) stimulate the creation of business through innovation networks. The theoretical approach, based on network theory and entrepreneurship theory, supports the basic idea of the importance of innovation networks in the process of business creation, since they allow remedying shortcomings and reinforcing positive aspects in order to influence the process of business creation. A questionnaire was developed for data collection, which was subsequently answered by nascent entrepreneurs belonging to higher education institutions, with 255 answers. The results obtained show that cooperation and development of relations with other actors of the innovation network emerge as the main ways of how HEIs encourage business creation, and show that HEIs' attitude for the creation of companies influences the decision of nascent entrepreneurs to go ahead with this process. The main factors that facilitate the creation of companies present in innovation networks are the network actors and organizational resources. Furthermore, with regard to identifying and analyzing obstacles to business creation based on innovation networks, it was found that the main factors are knowledge and location. The main conclusions of this research show the importance of HEIs in the phenomenon of business creation through innovation networks.